CHALLENGE IN TECHNOLOGICAL INNOVATION - Hakim, Arif Rahman (SIGMA TEKNIKA, 2020)
This article describes about the study based on document literature and documents review about the challenge facing in technological innovation. The writer has reviewed some reports and literarture relevance to this subject of the study. It is revealed that the challenge in technological innovation is to motivate youth to be interesting in study of Science, Technology, Engineering and Mathmatics (STEM).Â  While the government is required to support the technology development in term of policy, financial and regulatory.Â